Groundwater Quality Assessment for Drinking Purpose in Gulistan-e-Johar Town, Karachi, Pakistan - Khan, Adnan; Khan, Muhammad Akif (UIR PRESS, 2018)
The main objective of present study is to evaluate the groundwater quality of Gulistan-e-Johar Town for drinking. For this purpose, groundwater samples (n=18) through electrically pumped wells were collected from shallow aquifers (mean depth = 36 m). Collected samples were subjected to determine the physical characters (TDS, pH, temperature), major (Na, K, Ca, Mg, Cl, SO 4 , HCO 3 , and NO 3 ) and minor ions (Fe, Mn and F). Data reveal very high content of TDS (mean: 2862 mg/L) coupled with elevated concentration of Na (mean: 974.6 mg/L), Cl (mean: 545.3mg/L), SO 4 (mean: 600mg/L), Mn (mean: 0.04 mg/L) and F (mean: 1.7 mg/L). The results indicated that groundwater of Gulistan-e-Johar is not suitable for drinking purpose and may lead to dangerous health impacts. The WQI value of groundwater is found to be 183 which is also endorsing that groundwater of Gulistan-e-Johar is unfit for drinking purpose.